Regional dynamics of social partnership: political, legal and value characteristics - Natalia V. Fedorova, Sergey S. Shestopal, Ashkhen S. Aroyan, Alexander V. Ponedelkov, (Opción, 2019)
The subject of this work is the study of the level of development, key problems and directions for the development of social partnership via expert surveys conducted in 13 regions of the Russian Federation. As a result, the development of regions, the provision of positive social dynamics in the development of the latter is associated with the formation and stimulation of social partnership. In conclusion, the model of joint development of the key actors of the political and socio-economic processes is the most adequate in comparison with the liberal-democratic forms and practices, to solve many regional problems, conflicts and contradictions.